(untitled) (Research, Society and Development, 2021)
Introduction: Psychosocial aspects of work are sources of occupational stress, with impacts on mental health. There are few studies relating Common Mental Disorders (CMD) in restaurant workers. Objective: to analyze the presence and factors associated with Common Mental Disorders (CMD) in restaurant workers in Belo Horizonte, MG. Methodology: A cross-sectional, descriptive study was carried out, with a sample of 87 individuals who represented 72.5% of the workers distributed in four university restaurants. Results: Among the restaurant workers interviewed, 10.3% (n = 9) presented current Common Mental Disorders (CMD). A significant correlation was found between the presence of Common Mental Disorders (CMD), with gender, psychological and psychiatric monitoring, and with no significant correlation with the other variables studied (obesity, function, working hours). Conclusion: The results of this study indicate that the prevalence of Common Mental Disorders (CMD) among restaurant workers is a reality and that it requires intervention to promote a better quality of life for these individuals.